2019
DOI: 10.3390/v12010030
|View full text |Cite
|
Sign up to set email alerts
|

Influenza D Virus: Serological Evidence in the Italian Population from 2005 to 2017

Abstract: Influenza D virus is a novel influenza virus, which was first isolated from an ailing swine in 2011 and later detected in cattle, suggesting that these animals may be a primary natural reservoir. To date, few studies have been performed on human samples and there is no conclusive evidence on the ability of the virus to infect humans. The aim of this serological study was to assess the prevalence of antibodies against influenza D virus in human serum samples collected in Italy from 2005 to 2017. Serum samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 40 publications
1
52
0
Order By: Relevance
“…The antibodies the HI assay measure are those that block a functional interaction between the virus and the sialic acid receptor and as a result neutralize virus infection. HI assays involving virus-specific hyperimmune sera generated in rabbits, guinea pigs and sheep revealed no detectable crossreactivity between IDV and ICV, as reported in several studies [19,20,91]. Nevertheless, some level of cross-reactivity between IDV and ICV was observed in the HI assay when ferret sera were used.…”
Section: Zoonotic Potential Of Idvsupporting
confidence: 72%
See 2 more Smart Citations
“…The antibodies the HI assay measure are those that block a functional interaction between the virus and the sialic acid receptor and as a result neutralize virus infection. HI assays involving virus-specific hyperimmune sera generated in rabbits, guinea pigs and sheep revealed no detectable crossreactivity between IDV and ICV, as reported in several studies [19,20,91]. Nevertheless, some level of cross-reactivity between IDV and ICV was observed in the HI assay when ferret sera were used.…”
Section: Zoonotic Potential Of Idvsupporting
confidence: 72%
“…An earlier serosurvey in the USA showed that 1.3 % ( n =316) of the general human population had antibodies against IDV [4], Notably, in a more recent study, a very high seroprevalence of IDV was observed among workers with cattle exposure history (34 out of 35 people had IDV antibodies), as reported in a serological study in Florida, USA [20]. In addition, a more comprehensive seroprevalence study in Italy revealed that IDV antibodies were present and increased over time in the Italian population from 2005 to 2017 [91]. The results showed that low levels of antibodies against IDV were found in the years 2005–2007 (5.1 %–9.8 %), but these increased sharply in the years 2008–2010 (37.9–43.4 %) and 2013–2014 (41.0–46.0 %), followed by a decline in the subsequent years 2011–2012 and 2015–2017 [91].…”
Section: Zoonotic Potential Of Idvmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, a serological survey revealed that, apart from cattle and pigs, sheep, goats, horses, and camels were also susceptible to infection with IDV, suggestive of its broad cell tropism [14][15][16]. Furthermore, other serological studies have reported the detection of virus-specific antibody titers in human sera [7,17,18]. Thus, these findings suggest that this virus has zoonotic potential.…”
Section: Introductionmentioning
confidence: 82%
“…Indeed, it is important to highlight its ability to replicate and be transmitted among ferrets and guinea pigs, the gold standard for influenza studies animals [ 9 ] and its potential to infect a wide number of domestic mammal species. The few seroprevalence studies undertaken to date in humans have shown that the risk of transmission from infected cattle to humans may be very high, with peaks in humans that seem to follow IDV epidemics in animals [ 10 ]. Cattle-workers showed seroprevalence rates against IDV above 90%, almost five times higher than the control subjects without contact with cattle [ 11 ].…”
mentioning
confidence: 99%